2019
DOI: 10.1108/heswbl-04-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Differences in accounting students’ perceptions of their development of professional skills

Abstract: Purpose The purpose of this paper is to explore differences in South African accounting students’ perceptions of professional skills developed in an undergraduate accounting program. South Africa has a history of socio-economic inequality and racial injustice, leading to factors outside the classroom impacting educational outcomes. In particular, South African classes are heterogeneous, reflecting a diversity of race and language groups and students from differing schooling backgrounds. These differences neces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 57 publications
0
9
0
2
Order By: Relevance
“…The object of the research was the level of professional competences and soft skills of public administration employees used by them to effectively perform their job positions. Soft skills have been defined as the competences that each employee should have regardless of their profession [25,26]. The following soft skills have been examined: The professional competences have been defined in close connection with the relevant profession.…”
Section: Data and Proceduresmentioning
confidence: 99%
“…The object of the research was the level of professional competences and soft skills of public administration employees used by them to effectively perform their job positions. Soft skills have been defined as the competences that each employee should have regardless of their profession [25,26]. The following soft skills have been examined: The professional competences have been defined in close connection with the relevant profession.…”
Section: Data and Proceduresmentioning
confidence: 99%
“…Meanwhile, in recent studies, demographic characteristics of students were examined in terms of their effect on e-learning activities, and the findings showed that age and grades of students significantly influence their SE and professional skills (e.g., Dahalan et al, 2012;Duan et al, 2018;Jung and Lee, 2018;Thill et al, 2016;Zhang and Liu, 2019). Lastly, students' demographic characteristics were also found to affect their APC and their accounting skill development (Anjum, 2020;Hassan et al, 2020;Helm, 2015;Kirstein et al, 2019;Szadziewska et al, 2017;Yanto et al, 2011). Hence, this study proposes the moderating effect of students' demographic characteristics on the relationship between SE and APC and tests the following hypothesis;…”
Section: Student Demographics Moderates the Relationship Between Se A...mentioning
confidence: 99%
“…Menurut Chatman (1989) pekerjaan yang tidak sesuai dengan lingkungan nyaman menurut individu dapat meningkatkan ketidakpuasan kerja. Hal tersebut diakibatkan karena jika rutinitas yang terjadi dalam pekerjaan tidak sesuai dengan keinginin seseorang maka hal tersebut akan membuat semangat kerja menurun, sesuai dengan penelitian Kirstein et al, (2019) ini akan mempengaruhi persepsi mereka terhadapa profesi akuntan publik. Jika dilakukan pendekatan menggunakan teori perilaku terencana dan teori pengharapan maka mahasiswa akan berpikir dua kali untuk memilih pekerjaan dengan mempertimbangkan bagaimana lingkungan kerja suatu profesi yang akan mereka cari.…”
Section: Pendahuluanunclassified